DESENTRALISASI ASIMETRIS DAERAH ISTIMEWA YOGYAKARTA DALAM KETATANEGARAAN INDONESIA - Siregar, Ramadani; Fatimah, Siti; Ramadani Siregar; Siti Fatimah (JURNAL TAPIS, 2023)
Asymmetric decentralization is one answer to the practice of democracy in Indonesia, namely a historical continuity that started from the colonial period until now confirmed in the 1945 Constitution of the Republic of Indonesia. As a reality of regional government practice, constitutional juridical legitimacy is referred to in Article 18 A paragraph 1 and Article 18B paragraph. This research aims to determine the problem of asymmetric decentralization in Indonesia, especially in DI Yogyakarta.This research is qualitative research with a library research approach (library study) with descriptive methods.The research results show that the laws made are not yet in the best condition in establishing strong and clear rules.Article 7 paragraph 2 letter b and article 30 do not at all describe the essence of the privilege in question, regarding culture, special authority in Yogyakarta or spatial planning clearly not only includes physical space but also culture which is related to the philosophy of cosmological balance in terms of spatial planning